When students evaluate their curriculum: a few conclusions drawn from an international research programme - Lima, Laurent; Hadji, Charles (Papers. Revista de Sociologia, 2005)
To evaluate teaching is currently considered as compelling, both from an institutional and a moral viewpoint. However the conditions of such an evaluation have triggered strong debates: «Who? What? How? Drawing from which references? Which clues? Should the people assessed take part in the process? To what extent should the results be publicized?» (Demailly, 2001). For that reason we will first draw some guiding lines for teaching eva luation, trying to define its possible objects. Three main domains may be contemplated: teachers, activity, learning process, and the effects of the teaching/learning process. Drawing from an enquiry carried out in three European areas, by three research teams… We will be able to show that an evaluation of their courses by students is both possible and profitable. As a matter of fact, this inquiry has brought up valuable information about higher education pedagogy as concerns the three fields mentioned earlier and it also offers some suggestions likely to generate improvements. This survey has pointed out «problematic domains» (PD) where students meet with concrete and precise difficulties like feeling unable to participate actively in the lesson; and other domains for which projects are urgently needed with a view to improving learning conditions.